Perbandingan Lembaga Pemberantasan Narkotika: BNN (Indonesia) dan PDEA (Filipina) Ditinjau dari Aspek Kultural-Kognitif - Maulika Rahmatulaili; Muhammad Rafli Syahputra; Ester Yulianti Pakpahan; Putri Aksa Yemima; Rudiana Rudiana (Pusat Riset dan Inovasi Nasional, 2025)
Drug abuse and trafficking are transnational issues that require serious attention from various countries. Indonesia and the Philippines, two countries in Southeast Asia, have developed different institutional approaches in combating drugs through the Badan Narkotika Naional (BNN) and the Philippine Drug Enforcement Agency (PDEA). This study aims to compare both institutions from the cultural-cognitive pillar based on William Richard Scott’s institutional theory. The method used is descriptive qualitative research with a literature study approach. The results show that BNN prioritizes rehabilitative and educational approaches that are increasingly accepted as a reasonable treatment pattern in Indonesia. Meanwhile, PDEA implements a repressive approach that is supported by most of the Filipino society, despite being accompanied by human rights violations. These findings indicate that collective thinking frameworks and public legitimacy play a crucial role in shaping institutional strategies and impacts in each country. This study provides significant implications regarding how societal mindsets influence the effectiveness of drug eradication efforts.